Electromechanical impedance (EMI) measurements to infer features from the grinding process - Ferreira, Fabio Isaac [UNESP]; de Aguiar, Paulo Roberto [UNESP]; da Silva, Rosemar Batista; Jackson, Mark James; de Souza Ruzzi, Rodrigo; Baptista, Fabrício Guimarães [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Springer Nature, 2020)
This paper discusses the correlations between the electromechanical impedance (EMI) technique and grinding parameters. The EMI technique applied in grinding is novel and has the advantage of employing cheaper equipment and requiring a simpler monitoring system when compared to traditional techniques, such as acoustic emission. Experimental tests were conducted in a controlled environment to isolate the variables of interest, and real and imaginary parts of the impedance were investigated for several frequency bands. Strong correlations among EMI and equivalent chip thickness, roughness, and microhardness of the workpiece, as well as power signals, were found. The RMSD (root-mean-square deviation) index for the real part of the signature in the band 80–85 kHz showed good correlation with roughness and power, while the CCDM (correlation coefficient deviation metric) index for the imaginary part of 50–55 kHz showed good correlation with microhardness. Those correlations allow the user to infer information about the grinding process through indirect monitoring.
Keywords: Electromechanical impedance; Grinding; Piezoelectric transducer; Structural health monitoring; Surface quality